2015
DOI: 10.1016/j.jaip.2015.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Similar Efficacy with Omalizumab in Chronic Idiopathic/Spontaneous Urticaria Despite Different Background Therapy

Abstract: Omalizumab 300 mg was safe and effective in reducing CIU/CSU symptoms regardless of background therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 19 publications
6
45
0
7
Order By: Relevance
“…Real‐world experience also corroborates this: long‐term (>1‐year) use of omalizumab has been considered safe in two small retrospective studies and in individual case studies . Phase III data show a slight increase in sinusitis (4.9% vs. 2.1%), viral upper respiratory tract infection (0.5% vs. 0%), arthralgia (2.9% vs. 0.4%), headache (6.1% vs. 2.9%) and cough (2.2% vs. 1.2%) with omalizumab 300 mg compared to placebo . Anaphylaxis has been estimated to occur in 0.1–0.2% of patients with allergic asthma; however, no cases of anaphylaxis were reported in the phase III trials of omalizumab in CSU.…”
Section: Use Of Omalizumab For the Management Of Csu In The Real‐worlmentioning
confidence: 59%
See 2 more Smart Citations
“…Real‐world experience also corroborates this: long‐term (>1‐year) use of omalizumab has been considered safe in two small retrospective studies and in individual case studies . Phase III data show a slight increase in sinusitis (4.9% vs. 2.1%), viral upper respiratory tract infection (0.5% vs. 0%), arthralgia (2.9% vs. 0.4%), headache (6.1% vs. 2.9%) and cough (2.2% vs. 1.2%) with omalizumab 300 mg compared to placebo . Anaphylaxis has been estimated to occur in 0.1–0.2% of patients with allergic asthma; however, no cases of anaphylaxis were reported in the phase III trials of omalizumab in CSU.…”
Section: Use Of Omalizumab For the Management Of Csu In The Real‐worlmentioning
confidence: 59%
“…Response to omalizumab in the real‐world clinical setting in patients with CSU has been shown to be similar to, and in some cases better than that seen in the pivotal randomized controlled trials (Table ) …”
Section: Practical Management Of Urticaria With Omalizumab In the Reamentioning
confidence: 78%
See 1 more Smart Citation
“…Dear Editor , Omalizumab has been shown to be a very effective drug in treating chronic spontaneous urticaria (CSU), improving patients’ quality of life . The phase III clinical trials ASTERIA I/II and GLACIAL showed, respectively, 58·8% and 52·4% of patients achieving a twice‐daily average Urticaria Activity Score 7 (UAS7td) ≤ 6 at week 12 . Outside of clinical trials, the response varies between 77% and 83% .…”
Section: Demographic and Clinical Variables Of The Study Population (mentioning
confidence: 99%
“…Casale i wsp. [16] przeanalizowali dane z powyższych badań, porów-nując obie grupy pacjentów. Nie stwierdzono różnic w skuteczności omalizumabu w zależności od stosowanej terapii podstawowej PPS.…”
Section: Omalizumabunclassified